Pengaruh Bauran Pemasaran, Ekuitas Merek Terhadap Keputusan Pembelian Benih Cap Kapal Terbang di Jawa Barat - Dodi Supriatna; Dodik Ridho Nurrochmat; Idqan Fahmi (Jurnal Aplikasi Bisnis dan Manajemen, 2017)
Marketing tools known as the marketing mix, interacts with the brand equity in influencing consumer purchasing decisions. This study aims to analyze the level of marketing mix and brand equity and analyze the effect of the marketing mix with dimensions of brand equity. Presentation techniques and data analysis used in this research is descriptive analysis and Structural Equation Model (SEM). Research using depth interview technique. The experiment was conducted in West Java province with the number of respondents 137 vegetable farmers. Research shows that the product and the price has no effect on all dimensions of brand equity. Meanwhile, marketing channels and promotion effect on perceived quality, each with a loading factor of 0.516 and 0.715. Brand awareness and brand association has no effect on the decision. Only perceived quality influence on purchase decisions with a value of loading factor of 0.516. The study concluded that, perceived quality influences purchase decisions. Channel marketing and promotion affect perceived quality.